Metal Mesh Metasurfaces as Dual-Band Bandpass Filters for Terahertz Frequencies - Perov, A. (Advanced Electromagnetics, 2024)
In the paper, we propose a new strategy to design of metal mesh filters (MMFs) based on spatial symmetry analysis of bound states in the continuum(BICs) and manipulating and control with resonances, when BICs transformed to the resonances due to spatial perturbations in the MMF structure. The design of a dual-band polarization-insensitive terahertz bandpass filter with wide upper stopband characteristics using a single conducting layer patterned with rectangular holes is presented. The transmission response of the MMF with two poles is obtained to realize dual-band characteristics and three zeros to suppress the stopband. The proposed design has achieved broadband bandpass transmission characteristics under both TE and TM polarizations with canter frequencies at 0.516THz and 0.734THz and 3dB bandwidths of 25% and 17%, respectively, and upper stopband from 0.887THz to 1.6THz with over 10dB suppression.